O canto do Galo da Vila no Espírito Santo : a trajetória do Atlético Itapemirim e o seu processo de profissionalização no futebol - Silva, Mariana Schade da (2018)
This paper analyses the trajectory of Atletico Itapemirim a football club in the South of Espírito Santo, and its process of professionazation in the sports field. The Galo da Vila, as it Known was founded in 1965, having stayed for about 45 years in amateur and invisible football in the history of this sport in Espírito Santo, but in 2011 it became professionalized and has experience in recent years a rapid rise to the top of the capixaba soccer. In 2017, he became champion of the two largest state competitions Capixabão and Copa Espírito Santo. The research sought to describle and analyse the career path of the Galo da Vila and reflect on its process of ascension to the championship of Espírito Santo, based on the narratives of members of itsboard and three of its athletes. Such storytellers, principally directors and a principal athlete have noto only experience the club’s history of defeats and disappointments in their daily lives, but they have also experience the taste of ascension and victories in the recent history of Capixaba football.